From national liberation to radical democracy: Exploring the shift in the Kurdish liberation movement in Turkey. (October 2019) - Fadaee, Simin; Brancolini, Camilla
This paper argues that the (re)framing of the Kurdish movement from national liberation to radical democracy in Turkey has set the ground for a redefinition of strategies from ethnic rights to civil rights. In this sense, the Kurds have put forward a meta-political critique of society by going beyond ethnic claims. We show how, as the result of criticizing the neoliberal representative democracy and the capitalist state, the Kurdish liberation movement's strategies were transformed to advancing broader civil claims. Based on original research, we elaborate on three concrete expressions which have emerged as the result of this transformation: The Democratic Society Congress, the women's movement and the environmental movement. Finally, we explore the emancipatory potential of this shift for recognition of the rights of minorities in particular and for broader social change in general.